2009
DOI: 10.1112/blms/bdp021
|View full text |Cite
|
Sign up to set email alerts
|

‘High spots’ theorems for sloshing problems

Abstract: Abstract. We investigate several 2D and 3D cases of the classical eigenvalue problem that arises in hydrodynamics and is referred to as the sloshing problem. In particular, for a domain W ⊂ R 2 (canal's crosssection), where ∂W = F ∪ B and F (cross-section of the free surface of fluid) is an interval of the x-axis, whereas B (bottom's cross-section) is the graph of a negative function, the following result is proved. The fundamental eigenfunction u1 of the sloshing problem (the corresponding eigenvalue is simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…[3,Section 3], [26], [30]) one obtains the following domain monotonicity results for eigenvalues for both the Dirichlet-Steklov problem (2.1)-(2.3) and the sloshing problem (1.1)-(1.4). We omit the proofs of these results because they are very similar to the proofs of Propositions 3.…”
Section: Fundamental Eigenvaluementioning
confidence: 99%
See 1 more Smart Citation
“…[3,Section 3], [26], [30]) one obtains the following domain monotonicity results for eigenvalues for both the Dirichlet-Steklov problem (2.1)-(2.3) and the sloshing problem (1.1)-(1.4). We omit the proofs of these results because they are very similar to the proofs of Propositions 3.…”
Section: Fundamental Eigenvaluementioning
confidence: 99%
“…The other one treat fundamental eigenfunctions in troughs (their cross-sections are subject to the same condition), and some vertical axisymmetric containers. Moreover, it was shown in [26] that for vertical-walled containers with horizontal bottom the question about high spots is equivalent to the hot spots conjecture.…”
Section: Introductionmentioning
confidence: 99%
“…According to formula (2.1), the corresponding eigenfunction is f 1 (x, y, z) = u 0,1 (x, y), and it solves problem (2.2)-(2.5) for m = 0 and n = n 0,1 . Theorem 2.1 proved by Kulczycki & Kuznetsov (2009) where the trace u 0,1 (x, 0) attains its extremum values, say, (0, 0) and (a, 0) are the minimum and maximum points, respectively. Then, f 1 (x, 0, z) is equal to u 0,1 (0, 0) and u 0,1 (a, 0) on the whole edges…”
Section: High-spots Theorem For Troughsmentioning
confidence: 99%
“…First results about high spots for fundamental eigenfunctions of the sloshing problem were obtained by Kulczycki & Kuznetsov (2009), who proved some theorems about the location of these points in the two-dimensional case and for some vertical axisymmetric containers. Moreover, it was shown that for verticalwalled containers with a horizontal bottom, the question of whether high spots is equivalent to the 'hot spots' conjecture of J. Rauch (see Burdzy (2006) for a survey of results about the latter conjecture).…”
Section: Introductionmentioning
confidence: 99%
“…The Steklov eigenvalues have a number of domain monotonicity properties that bear directly on the present discussion (cf., e. g., Kulczycki and Kuznetsov (2009)). We recall that the Steklov eigenvalues admit the variational characterization (cf., e. g., Lamberti and Provenzano (2013); Bogosel et al (2017); Girouard and Polterovich (2017)) (30) σ n = inf…”
Section: Monotonicity With Respect To Cuttingmentioning
confidence: 99%